PRODUKSI KEDELAI (Glycine max L. Merill) DENGAN PEMBERIAN BERBAGAI SUMBER HARA N DAN PERBEDAAN KONDISI AIR TANAH - Muhamad Juandi; Yaya Hasanah; Sanggam Silitonga (Universitas Sumatera Utara, 2013)
The objective of research was to know the production of soybean with application of variousN sources and differences of groundwater conditions. Research conducted at the Screen HouseFaculty of Agriculture, University of Sumatera Utara, Medan on February until May 2012, using arandomized block design factorial with two factors and three replications. The first factor wassources of nitrogen consisted of without N sources, inorganic N sources (Urea), biological Nsources (Bradyrhizobium japonicum), organik N sources (straw compost) (50 g/polybag), andmanure (50 g / polybag). The second factor was groundwater conditions consisted of 60%, 70% and80% field capacity. The results showed that groundwater conditions were significantly difference todry weight seeds/plant and pods containing, Effect of N source and interaction between applicationof various N sources